2022
DOI: 10.26650/eurjbiol.2022.1111191
|View full text |Cite
|
Sign up to set email alerts
|

Myrtus communis L. Extract Ameliorates High Fat Diet Induced Kidney and Bladder Damage by Inhibiting Oxidative Stress and Inflammation

Abstract: Objective: Obesity is associated with many diseases, including urinary system disorders such as chronic kidney disease and overactive bladder syndrome. Myrtus communis L. (MC) extract has been reported to have antioxidant and anti-inflammatory effects. The aim of this study was to investigate the protective effects of MC extract on high-fat diet (HFD)-induced kidney and bladder damage. Materials and Methods:Wistar albino male rats were divided into three experimental groups: control, HFD and HFD+MC. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Also, previous studies have demonstrated significant alterations in lipid profiles such as an increase in serum triglyceride and cholesterol and a decrease in HDL levels in obese animals [7,17]. MC treatment ameliorate biochemical alterations significantly and prevented dyslipidemia in HFD-induced obese rats [17]. Parallel to these findings, our study revealed an increase in triglyceride and cholesterol levels and a decrease in HDL levels in the blood serum, and MC treatment reversed these alterations.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Also, previous studies have demonstrated significant alterations in lipid profiles such as an increase in serum triglyceride and cholesterol and a decrease in HDL levels in obese animals [7,17]. MC treatment ameliorate biochemical alterations significantly and prevented dyslipidemia in HFD-induced obese rats [17]. Parallel to these findings, our study revealed an increase in triglyceride and cholesterol levels and a decrease in HDL levels in the blood serum, and MC treatment reversed these alterations.…”
Section: Discussionsupporting
confidence: 87%
“…The present study showed that MC treatment reduces the body weight in HFD-induced obese rats. Also, previous studies have demonstrated significant alterations in lipid profiles such as an increase in serum triglyceride and cholesterol and a decrease in HDL levels in obese animals [7,17]. MC treatment ameliorate biochemical alterations significantly and prevented dyslipidemia in HFD-induced obese rats [17].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations